Predictors of First-Time NCLEX-RN Pass Rate in Accelerated Bachelor of Science in Nursing Students. - Mahmoud, Khadejah F.; Zhao, Jian; Kyung Kim, Do; Hui, Vivian; Kitutu, Julius (Journal of Nursing Education, 2024)
Background: An accelerated Bachelor of Science in Nursing (ABSN) program was introduced in an effort to reduce the nursing shortage in response to the growing health demands. Nursing educators strive to examine factors that promote students' success in passing the National Council Licensure Examination for Registered Nurses (NCLEX-RN) on their first attempt. However, little is known about which factors predict the NCLEX-RN first-time pass rate of ABSN students. Method: This descriptive retrospective study examined academic and nonacademic indicators (e.g., age) that can predict ABSN students' NCLEX-RN first-time pass rates between 2008 and 2019. Results: A total of 591 ABSN students were included in the study. Both GRE (Graduate Record Examination) verbal reasoning scores (p <.001) and cumulative grade point averages (p <.001) were significant predictors. Conclusion: The findings of this study can help inform ABSN programs in terms of admission criteria and curriculum consideration for including standardized tests to improve ABSN students' NCLEX-RN first-time pass rate. [J Nurs Educ. 2024;63(1):10–16.]